The Christianization of the Romance population in the Balkans in the light of historical and linguistic facts - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2011)
The article concerns the process of Christianization among the Romance-speaking population of the Balkans, above all the ancestors of the Romanians and Vlachs. The author analyzes the problem of the origins of Romanian Christianity, which has long been the subject of historiographical disputes and ideological interpretations. The aim of the article is to verify traditional views on the Christianization of the Romance-speaking population through a comparison of historical and linguistic data. The subject is important for research on the history of the Balkans, the Romanization of the region, and the formation of Romanian identity. The author employs historical and linguistic analysis, examining among other things religious terminology preserved in the Romanian and Albanian languages. The article demonstrates that the Christianization of the Balkan provinces began already in Roman times, while later political and cultural transformations led the Romanians to adopt the Byzantine-Slavonic rite. Analysis of religious vocabulary points to a limited but fundamental body of Latin terms connected with Christianity. The results of the analysis indicate that the Christianization of the Balkans was a long-term and multi-stage process, and that the traditional national narrative requires partial reinterpretation.